2019
DOI: 10.1016/j.redox.2018.101068
|View full text |Cite
|
Sign up to set email alerts
|

Adropin protects against liver injury in nonalcoholic steatohepatitis via the Nrf2 mediated antioxidant capacity

Abstract: Adropin, a secretory signal peptide, has shown beneficial effects on improving glucose homeostasis and dyslipidemia. However, whether this peptide affects nonalcoholic steatohepatitis (NASH) has remained unclear. In this study, the serum adropin levels, liver injury and oxidative stress were measured in diet-induced NASH mice. Adropin knock-out mice and palmitate treated primary hepatic cells were used to investigate the influence of adropin on liver injury. Our results show that serum adropin levels were decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 42 publications
(47 reference statements)
2
84
1
Order By: Relevance
“…Furthermore, mice with adropin deficiency have enhanced hepatic steatosis, fibrosis, as well as inflammation (non-alcoholic steatohepatitis-NASH) when fed methionine-choline deficient or western diets. In contrast, synthetic adropin attenuates NASH development in mice [67]. Notably, protective effects of adropin on hepatocytes injury were also confirmed in in vitro cultured hepatocytes.…”
Section: Adropin In Liver Diseasementioning
confidence: 72%
See 2 more Smart Citations
“…Furthermore, mice with adropin deficiency have enhanced hepatic steatosis, fibrosis, as well as inflammation (non-alcoholic steatohepatitis-NASH) when fed methionine-choline deficient or western diets. In contrast, synthetic adropin attenuates NASH development in mice [67]. Notably, protective effects of adropin on hepatocytes injury were also confirmed in in vitro cultured hepatocytes.…”
Section: Adropin In Liver Diseasementioning
confidence: 72%
“…Notably, protective effects of adropin on hepatocytes injury were also confirmed in in vitro cultured hepatocytes. Investigation of molecular signaling conferring beneficial effects of adropin peptide against liver damage showed that adropin promotes Nfr2 transcription activity [67]. Downregulation of serum adropin levels was also reported in patients with non-alcoholic liver fatty disease [68].…”
Section: Adropin In Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Whereas DPPH comprises stable free radical molecules, hydrogen peroxide (H 2 O 2 ) is one of ROS which is generated as a short-lived product in biochemical processes, such as β-oxidation of long chain fatty acids [29] . And ROS appears to be a feature of liver diseases [30,31] . Therefore, leaves, not stems, of PCP are an ideal material for use as a liver diseases treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Adropin activates Nrf2 signaling in nonalcoholic steatohepatitis (NASH) and plays a role in decreasing reactive oxygen species (ROS) production from liver mitochondria. So, it may protect mitochondrial function to alleviate oxidative stress and apoptosis and thus protect against liver injury and prevent the NASH progression [44]. Figure 2: Regulatory mechanisms of adropin for immune cells.…”
Section: Association Between Adropin and Other Inflammatory Diseasesmentioning
confidence: 99%